2003
DOI: 10.1289/ehp.5887
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative organophosphate pesticide exposure and risk assessment among pregnant women living in an agricultural community: a case study from the CHAMACOS cohort.

Abstract: Approximately 230,000 kg of organophosphate (OP) pesticides are applied annually in California's Salinas Valley. These activities have raised concerns about exposures to area residents. We collected three spot urine samples from pregnant women (between 1999 and 2001) enrolled in CHAMACOS (Center for the Health Assessment of Mothers and Children of Salinas), a longitudinal birth cohort study, and analyzed them for six dialkyl phosphate metabolites. We used urine from 446 pregnant women to estimate OP pesticide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
64
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 26 publications
2
64
2
1
Order By: Relevance
“…Pesticide exposures to infants and children from food, water, and residential sources have been well documented (Woody, 1984;Zwiener and Ginsburg, 1988;Fenske et al, 1990;Morgan et al, 2001;Castorina et al, 2003;Colt et al, 2003;Rohrer et al, 2003;Hore et al, 2005;Boone et al, 2006;Chambers et al, 2007). However, one area that does not seem to have been appreciably explored is the possibility that residues of insecticides remaining on pet fur from flea control treatments could be a significant source of pesticide exposure in children.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticide exposures to infants and children from food, water, and residential sources have been well documented (Woody, 1984;Zwiener and Ginsburg, 1988;Fenske et al, 1990;Morgan et al, 2001;Castorina et al, 2003;Colt et al, 2003;Rohrer et al, 2003;Hore et al, 2005;Boone et al, 2006;Chambers et al, 2007). However, one area that does not seem to have been appreciably explored is the possibility that residues of insecticides remaining on pet fur from flea control treatments could be a significant source of pesticide exposure in children.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that children can be exposed to pesticides from numerous sources such as carpet, clothing, house dust and toys in treated houses (Fenske et al, 1990;Castorina et al, 2003;Colt et al, 2003;Rohrer et al, 2003;Hore et al, 2005). Pesticide exposures have also been documented from children who played outside in treated lawns and/or gardens (Woody, 1984;Morgan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Through the National Human Exposure Assessment Survey (NHEXAS) (Sexton et al, 1995), the Children's Total Exposure to Persistent Pesticides and other Persistent Organic Pollutants (CTEPP) (USEPA, 2002), and other programs, the US EPA is developing databases on exposures of human populations to a wide range of pollutants in air, water, food, soil, and indoor/residential environments, and over a wide range of space and time scales. The University of California, Berkeley Center for the Health Assessment of Mothers and Children of Salinas (CHAMACOS) is collecting biomarkers in farming communities for pesticides and other important pollutants from mothers and their newborn children from conception through early childhood (Castorina et al, 2002).…”
Section: Introductionmentioning
confidence: 99%